Systems-Theoretic Process Analysis of space launch vehicles. Issue 3 (September 2018) - Rising, John M.; Leveson, Nancy G.
Abstract: This article demonstrates how Systems-Theoretic Process Analysis (STPA) can be used as a powerful tool to identify, mitigate, and eliminate hazards throughout the space launch system lifecycle. Hazard analysis techniques commonly used to evaluate launch vehicle safety use reliability theory as their foundation, but most modern space launch vehicle accidents have resulted from design errors or other factors independent of component reliability. This article reviews safety analysis methods as they are applied to space launch vehicles, and demonstrates that they are unable to treat many of the causal factors associated with modern launch accidents. Next, it describes how STPA can be applied to the design of space launch vehicles to treat these casual factors. Safety-guided design with STPA is then demonstrated with a hypothetical small-lift launch vehicle, launch safety system, and upper stage propulsion system.